Arbeiter-Marseillaise [Bladmuziek] - Rouget de Lisle, Claude Joseph; Audorf, Jacob (Stuttgart : J.H.W. Dietz, 1900)
Bibliotheek Camille Huysmans
Duits
Partituur
Keywords: koorwerken; arbeidersliederen; Duitsland